Promoting renewable energy and energy efficiency in Africa: a framework to evaluate employment generation and cost effectiveness. (7th March 2017) - Cantore, Nicola; Nussbaumer, Patrick; Wei, Max; Kammen, Daniel M
Abstract: The ongoing debate over the cost-effectiveness of renewable energy (RE) and energy efficiency (EE) deployment often hinges on the current cost of incumbent fossil-fuel technologies versus the long-term benefit of clean energy alternatives. This debate is often focused on mature or 'industrialized' economies and externalities such as job creation. In many ways, however, the situation in developing economies is at least as or even more interesting due to the generally faster current rate of economic growth and of infrastructure deployment. On the one hand, RE and EE could help decarbonize economies in developing countries, but on the other hand, higher upfront costs of RE and EE could hamper short-term growth. The methodology developed in this paper confirms the existence of this trade-off for some scenarios, yet at the same time provides considerable evidence about the positive impact of EE and RE from a job creation and employment perspective. By extending and adopting a methodology for Africa designed to calculate employment from electricity generation in the U.S., this study finds that energy savings and the conversion of the electricity supply mix to renewable energy generates employment compared to a reference scenario. It also concludes that the costs per additional job created tend to decrease with increasing levels of both EE adoption and RE shares.